FORMATION AND IDEOLOGICAL CHARACTERISTICS OF THE SOVIET-ERA MASS MEDIA IN UZBEKISTAN (Global Conference on Multidisciplinary Research and Innovation, 2026)
This article analyzes the features of the formation and development of mass media in Uzbekistan during the Soviet period, with particular emphasis on press and publishing activities. Based on bibliographic indexes, the systematic state of periodical press and scientific publications in the republic is examined. The role of ideological control, censorship, and the practice of “silence” in information policy is revealed. The impact of compulsory subscription and one-sided interpretation of information on public consciousness is also discussed. Additionally, the article briefly analyzes changes that emerged in the information space on the eve of the policy of glasnost.
Keywords: Soviet period, Uzbek press, information policy, ideological control, censorship, bibliographic indexes, periodical publications, compulsory subscription, mass communication, glasnost policy.